Effect of Some Micronutrients on Damage Compensation and Yield Parameters in Okra. - Syed Shahzad Ali,; Wazhar Ali Pusio,; Huma Rizwana,; S. Shahbaz Ali,; Shifarash Ghouri,; S. Sohail Ahmad, (Journal of Basic & Applied Sciences, 2012)
The effect of micronutrients on damage compensation and yield components of okra was investigated, using three foliar sprays (at 15 days interval) of Effective microorganisms (EM-1), Wokozim and Kissan Supreme Tonic (KST). Weekly observations on sucking complex (thrips, jassid, whitefly) and pod borers were carried out. The yield ha-1 of green pods was recorded to ascertain the compensation of the damage done by the insect pests. The damage done by sucking complex and borers was markedly compensated by the micronutrients, and okra pod yield in EM-1, Wokozim and KST sprayed plots were 10911, 9507 and 8948 kg ha-1, respectively as compared to 8034 kg ha-1 in control. The effect of micronutrients on crop growth and subsequently on sucking complex infestation was significant and thrips, jassid, whitefly and borer infestation was relatively lesser in plots sprayed with micronutrient as compared to the control. KST was most effective in damage compensation of sucking complex and borers with highest okra green pod yield (P<0.01), followed by Wokozim and EM-1 when compared with control.